2019
DOI: 10.3389/fnins.2019.00712
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Analysis Reveals Epigenetic Pattern of SH2B1 in Chinese Monozygotic Twins Discordant for Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder. Aberrant DNA methylation has been observed in ASD but the mechanisms remain largely unknown. Here, we employed discordant monozygotic twins to investigate the contribution of DNA methylation to ASD etiology. Genome-wide DNA methylation analysis was performed using samples obtained from five pairs of ASD-discordant monozygotic twins, which revealed a total of 2,397 differentially methylated genes. Further, such gene list was annotated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…The study by Wong et al (2014) described methylation differences within each pair of discordant twins that were generally family specific as well as group differences between the combined cases and controls. The latter study by Liang et al (2019) reported more than 2300 DAGs between discordant Chinese MZ twins that were associated with a number of KEGG pathways, including the mTOR, axon guidance, and neurotrophin signaling pathways identified in our study. Interestingly, 10 of the 35 neurotrophin signaling genes identified by Liang et al (2019) are also represented in this study.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The study by Wong et al (2014) described methylation differences within each pair of discordant twins that were generally family specific as well as group differences between the combined cases and controls. The latter study by Liang et al (2019) reported more than 2300 DAGs between discordant Chinese MZ twins that were associated with a number of KEGG pathways, including the mTOR, axon guidance, and neurotrophin signaling pathways identified in our study. Interestingly, 10 of the 35 neurotrophin signaling genes identified by Liang et al (2019) are also represented in this study.…”
Section: Discussionmentioning
confidence: 57%
“…It should be noted that the use of discordant MZ twins is particularly advantageous for methylation studies in that the identical genotype allows for better resolution of epigenetic factors associated with a complex disorder. Since the study by Nguyen et al (2010), two other studies employing discordant MZ twins have reported genome-wide differences in DNA methylation associated with ASD (Liang et al, 2019; Wong et al, 2014). The study by Wong et al (2014) described methylation differences within each pair of discordant twins that were generally family specific as well as group differences between the combined cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al. [ 108 ], analyzed 5 ASD-discordant monozygotic twins and found 2,397 differentially methylated genes. Among these genes, the methylation of SH2B1 gene was further studied.…”
Section: Epigenetics Of Autism Spectrum Disordermentioning
confidence: 99%
“…Later, many researchers started using “bisulfite” to differentiate cytosine and methylated cytosine in studies that examine DNA methylation (Kinoshita et al 2013 ; Liang et al 2019 ). With bisulfite, cytosine is deaminated and converted to uracil, while methylated cytosine is left in its original state.…”
Section: Mz Studies Of Molecular Geneticsmentioning
confidence: 99%
“…The similarity of the genetic information in MZs provides a useful means for determining the disorder-causing role of environmental factors. In recent years, studies on the differences between genomic and epigenomic characteristics of MZs have led to the development of new approaches for elucidating the etiology of psychiatric disorders (Liang et al 2019 ; Morimoto et al 2017 ). The current paper focuses on epidemiological and molecular genetic research studies in MZs with the purpose of unravelling useful insights on factors that can lead to SCZ and ASD.…”
Section: Introductionmentioning
confidence: 99%